Effect of L-Glycine on Growth Performance and Economics of Commercial Broiler Chicken - Shisodiya, Mayur; Lonkar, Vijaysinh; Kadam, Avinash S; Mote, Chandrashekhar; Jadhav, Sameer; Kadam, Bapurao (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Study was conducted for six weeks on 240, day-old Cobb-430Y strain broiler chicks randomly assigned to four groups (60 chicks per group) containing three replicates. Group ‘A’ was Negative Control (NC) contained 3% Low Protein (LP) [19.50, 18.00 and 16.50% Crude Protein (CP) for broiler pre-starter (BPS), starter (BS) and finisher (BF) phases, respectively] than Positive Control (PC) group ‘B’. Group B contained Normal Protein (NP) [22.50, 21.00, and 19.50% CP] as per strain requirement. No L-Glycine was added to NC and PC diets. Group ‘C’ (NC+Gly1) was formed by adding 0.640, 0.810, and 0.630% L-Glycine in NC diet to arrive 2.30, 2.30, and 2.00% Digestible (Dig.) Gly + Ser levels while group ‘D’ (NC+Gly2) was formed by adding 0.755, 0.985, and 0.740% L-Glycine in NC diet to arrive 2.40, 2.40, and 2.10% Dig. Gly + Ser levels in BPS, BS, and BF diets, respectively. Dig. Gly + Ser levels of NC group were 1.71, 1.56, and 1.43%; and of PC group were 2.02, 1.91, and 1.76%, respectively for BPS, BS and BF diets. Ratio of Dig. Met, Thr, Trp, Arg, and Val. to Lys. were balanced (AA-balanced) in all diets. All diets were isocaloric (3010, 3100, and 3200 kcal ME /kg feed for BPS, BS, and BF, respectively). Results showed that the L-Glycine supplementation in AA-balanced 3% LP diet significantly (p≤0.05) improved overall BW, WG, and FCR in broilers. Dig. Gly + Ser levels of 2.30, 2.30, and 2.00% in AA-balanced 3% LP diets (0.640, 0.810, and 0.630% L-Glycine) in BPS, BS, and BF phases, respectively, were found to be cost-effective for improving BW, WG, and FCR with less feed intake. Study concludes that the L-Glycine supplementation is recommended to maintain Dig. Gly + Ser levels of 2.30, 2.30, and 2.00% in BPS, BS, and BF phases for cost-effective formulation with a reduction of 3% CP in a standard commercial broiler diet.